Slovenska evangeličansko-luteranska cerkev svetega Ivana v Betlehemu, Pensilvanija, ZDA - Kuzmič, Mihael (Dve domovini, 1996)
In this article the author gives a presentation of the Prekmurian Protestant emigrants in Betlehem, Pennsylvania, who are gathered in their faith in the Slovene Evangelical Church of Saint John. After immigrating in the first decade of this century they organized themselves into an independant parish as early as 1910. They created a strong material base and had an active religious and (to a certain extent) community life, well organized cultural activities and societies, and variegated literary activities under the leadership of pastors William Lambert, Dr Ernest Stiegler and Dr Frank Flisser, all of whom spoke the Prekmurian dialect. Through their activities they succeeded in uniting their Prekmurian compatriots in the United States and in maintaining close ties with their old homes and the homeland of their ancestors.
Keywords: evangeličanska cerkev; luteranstvo; Pensilvanija; Prekmurje; Slovenci; Slovenes; slovenski izseljenci; United States of America; ZDA